Anterior Uveitis Associated with Human Herpesvirus 7 Infection Diagnosed by Multiplex Polymerase Chain Reaction Assay: A Case Report. (7th February 2023) - Shirahama, Shintaro; Tanaka, Rie; Kaburaki, Toshikatsu
ABSTRACT: Background: Herpetic anterior uveitis (AU) is usually caused by the herpes simplex virus, varicella-zoster virus, and cytomegalovirus. Herein, we report a case of herpetic AU associated with human herpesvirus 7 (HHV-7) infection. Study Design: A case report Case presentation: A 49-year-old female patient presented with complaints of blurred vision and hyperemia in the right eye. Slit-lamp examination revealed bilateral fine and a few small white keratic precipitates (KPs), Descemet membrane folds in the right eye, and severe and mild cellular infiltration in the anterior chamber of the right and left eye, respectively. HHV-7 viral DNA was detected by a polymerase chain reaction assay of an aqueous humor sample. The AU improved significantly with topical steroids. Conclusion: We report a rare case of herpetic AU characterized by fine and small white KPs in which only HHV-7 DNA was detected in the aqueous humor.